Designing a resource‐stratified, phased implementation strategy for breast health care services in India. (29th April 2020) - Kumar, Somesh; Srivastava, Ashish; Srivastava, Ashish Kumar; Srivastava, Vineet; Nair, Tapas Sadasivan; Usmanova, Gulnoza; Singh, Ravikant; Sood, Bulbul; Ginsburg, Ophira
Abstract : Background: Breast cancer is the most common cancer among women in India. Jhpiego, a not‐for‐profit health organization, is providing technical assistance for developing an evidence‐based model of breast health care in the states of Uttar Pradesh and Jharkhand in India. Methods: A situational assessment of breast health care services using validated tools was conducted in the 2 states. Results: Findings of the assessment were presented to the Breast Health Technical Advisory Committee comprised of subject experts and government functionaries. The committee, guided by Breast Health Global Initiative resource‐stratified guidelines, developed a conceptual framework for integration of breast health services into the existing health system. This conceptual framework was presented to the Technical Advisory Groups (TAGs) of the respective state governments. Each TAG then developed an operationally feasible, contextually appropriate implementation plan in alignment with the national guidelines for noncommunicable diseases. This implementation plan guided the rollout of the breast health care program in the Lucknow (Uttar Pradesh) and Ranchi (Jharkhand) districts. Conclusions: Early results from the implementation suggest that it is feasible to integrate the breast health care pathway with the ongoing National Cancer Control Program of India. Abstract : A situational analysis of breast health care systems in 2 states in India is used to develop a conceptual framework to guide the implementation of breast health care programs in both states in partnership with policy makers, subject experts, and local government. The initial results from the implemented health care programs are presented.